Self-Perceived Cooking Skills in Emerging Adulthood Predict Better Dietary Behaviors and Intake 10 Years Later: A Longitudinal Study - Utter, Jennifer; Larson, Nicole; Laska, Melissa N.; Winkler, Megan; Neumark-Sztainer, Dianne (Journal of nutrition education and behavior, 2018)
To determine whether perceived cooking skills in emerging adulthood predicts better nutrition a decade later. Data were collected as part of the Project Eating and Activity in Teens and Young Adults longitudinal study. Participants reported on adequacy of cooking skills in 2002–2003 (age 18–23 years) and subsequently reported on nutrition-related outcomes in 2015–2016 (age 30–35 years) (n = 1,158). Separate regression models were used to examine associations between cooking skills at age 18–23 years and each subsequent outcome. One fourth of participants described their cooking skills as very adequate at 18–23 years, with no statistically significant differences by sociodemographic characteristics. Reports of very adequate cooking skills at age 18–23 years predicted better nutrition-related outcomes 10 years later, such as more frequent preparation of meals including vegetables (P < .001) and less frequent fast food consumption (P < .001). Developing adequate cooking skills by emerging adulthood may have long-term benefits for nutrition over a decade later. Ongoing and new interventions to enhance cooking skills during adolescence and emerging adulthood are warranted but require strong evaluation designs that observe young people over a number of years.